Are the last grade medical students aware of the danger of synthetic cannabinoids?. (February 2016) - Beyhun, Nazim Ercument; Can, Gamze; Topbas, Murat; Cankaya, Sertac; Ketenci, Huseyin Cetin
Abstract: Synthetic cannabinoids are drugs which are increasingly used by especially adolescents and young people. In recent years hospital admissions even concluding with deaths have been observed. Therefore, the awareness of medical students, who will be in challenge with this new drug abuse, is an important issue. The aim of this study is to figure out the awareness of the last grade medical students and its correlates. This is a questionnaire based descriptive study with the participation of 148 students at Karadeniz Technical University Medical Faculty, Turkey. An awareness score was produced to measure awareness (cronbach alpha = 0.67). The 17.6% (26/148) of students who reported not knowing what synthetic cannabinoids were and hearing the name for the first time in this study. The 16.4% of students assumed that synthetic cannabinoid use was legal, and 16.2% assumed that synthetic cannabinoids are not drugs. The internet (including social media) (48.6%) and pharmacology lectures (40.5%) were identified as the most stated sources of information. The students who have synthetic cannabinoid user friends and social media account have significantly higher awareness scores (p < 0.05 for both). Last grade medical students have a lack of awareness towards synthetic cannabinoids which is an increasing threat that they have to challenge. Highlights: There is a lack of awareness among medical students. Internet was stated as the most common source of knowledge. Having a synthetic cannabinoid user friend is a significant factor of awareness. Having a social media account is a significant factor of awareness.